2000
DOI: 10.1038/sj.ijo.0801427
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of haemostatic risk factors for coronary heart disease in obese children and adolescents

Abstract: OBJECTIVE: To investigate the contribution of serum lipids, parameters of glucose metabolism, body composition and cardiovascular ®tness to the variance of several haemostatic risk factors for coronary heart disease (CHD) in obese children and adolescents. SUBJECTS AND MEASUREMENTS: Forty-two healthy, obese children and adolescents (20 male, 22 female, age 12.6 AE 3.2 y; body mass index (BMI), 30.4 AE 5.3 kgam 2 ), were screened for haemostatic and metabolic risk factors for CHD. Thirty-®ve of the participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 41 publications
1
21
1
Order By: Relevance
“…By serving as a carrier for factor VIII, vWF-Ag may coordinate formation of the fibrin-and platelet-rich thrombus at the site of endothelial cell injury as well [39]. There have been studies that reported increased levels of vWF-Ag in the CI confidence interval, FB fibrinogen, IR insulin-resistant, NIR non insulin-resistant, OR odds ratio, PAI-1 plasminogen activator inhibitor-1-antigen, vWF-Ag von Willebrand factor-antigen obese pediatric population and significant positive associations between vWF-Ag levels and the BMI [26,62]. In the present study, insulin resistance was found to increase the possibility of detecting abnormally high vWF-Ag levels by 4.8 times.…”
Section: Discussionmentioning
confidence: 98%
“…By serving as a carrier for factor VIII, vWF-Ag may coordinate formation of the fibrin-and platelet-rich thrombus at the site of endothelial cell injury as well [39]. There have been studies that reported increased levels of vWF-Ag in the CI confidence interval, FB fibrinogen, IR insulin-resistant, NIR non insulin-resistant, OR odds ratio, PAI-1 plasminogen activator inhibitor-1-antigen, vWF-Ag von Willebrand factor-antigen obese pediatric population and significant positive associations between vWF-Ag levels and the BMI [26,62]. In the present study, insulin resistance was found to increase the possibility of detecting abnormally high vWF-Ag levels by 4.8 times.…”
Section: Discussionmentioning
confidence: 98%
“…87 Studies in children and adolescents have demonstrated a close relationship between fibrinogen, obesity, and physical fitness 88 -90,118,119,231,233 ; this in turn is implicated in cardiovascular morbidity and mortality later in life. 80,91 The underlying pathophysiological mechanisms for these alterations, however, remain elusive. Studies in children have reported that the increased plasma fibrinogen is due primarily to an increase in its fractional synthesis rate, 119,120 a phenomenon that does not occur in the elderly.…”
Section: Hemostasis and Thrombosismentioning
confidence: 99%
“…In this regard, elevated plasma concentrations of von Willebrand factor, t-PA and PAI-1 could be predictors of myocardial infarction and stroke incidence in older or in cardiac patients [28] . However, fibrinolysis is increased during 2 h triathlon where it neutralizes the increase in thrombin generation [29] , and increased D-dimer activity in healthy individuals is a marker of hydrolyzing the cross-linked fibrin by plasminogen which is generated from plasmin by t-PA.…”
mentioning
confidence: 99%